Illocutionary Acts in Recorded Presentations of English Education Master's Program Students - Dewanty, Monika; Bram, Barli (English Department, Faculty of Humanities, Andalas University, 2023)
This study aims to identify the illocutionary acts used by English Education Master’s Program students and the underlying reasons for them to use the acts in their recorded presentations. There is little study on master’s degree students, especially in the pandemic era. Therefore, this study attempted to identify the illocutionary acts performed by master’s degree students in the recorded presentation. This study used qualitative research in order to collect and analyze the data. Searle’s (1979) theory of the illocutionary act is used. The data was taken from the videos which were transcript. The transcription was used to analyze the illocutionary acts used by the students. The qualitative data showed that the students mainly used representatives (66%), directives (26%), and expressive acts (8%) in the video 1 of the recorded presentation. Similarly, in the second video, the student used representatives (68%), directives (25%), and expressive (6%). Besides, none of the videos were showing the students’ commissive and declarative acts. Results showed that the students used it for explaining to the audiences about facts or theories and examples.